Median voters and power resources revisited: a composite model of inequality - Wong, Mathew Y. H. (Luxembourg, 2013)
"This paper explains redistribution and income inequality by revisiting traditional approaches. First, despite the popularity of two dominant theories, the median voter hypothesis (the Meltzer-Richard model) and power resources theory, they are thought to have contrasting predictions and have seldom been incorporated under a single framework. We develop a composite model of inequality by accommodating their core arguments. This study also analyzes stages of inequality formation, such as market wage inequality and redistribution, and adds in a dynamic component to the model, completing the cycle of inequality. The model is supported empirically with data from 18 OECD countries from 1970 to 2006. We demonstrate the joint relevance and significance of the two theories, showing that they are not necessarily mutually exclusive."